Iain Boyd White and David Frisby, eds. Metropolis Berlin: 1880-1940. Berkeley: University of California Press, 2012. - Tyler Carrington (Studies in 20th & 21st Century Literature, 2017)
Review of Iain Boyd White and David Frisby, eds. Metropolis Berlin: 1880-1940. Berkeley: University of California Press, 2012.
Keywords: Berlin; Metropolis; turn-of-the-century; Kaiserreich; Weimar; Nazi; Wilhelmine; urban; Grossstadt